2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081209
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of missing samples in fetal heart rate recordings with Gaussian processes

Abstract: Abstract-Missing samples are very common in fetal heart rate (FHR) recordings due to various reasons including fetal or maternal movements and misplaced electrodes. They introduce distortions and cause difficulties in their analysis. In this paper, we propose a Gaussian process-based method that can utilize other intrapartum signals (e.g., uterine activity and maternal heart rate) to recover the missing samples in FHR recordings. The proposed approach was tested on a short real FHR recording segment and its pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…With this information, the predictive performance of the method should be better than that of using information from past values of FHR alone. This is consistent with our observation in [19]. There we showed that adopting information from UA signals helps in recovering missing samples of FHR tracings.…”
Section: Real Data: Ctg Segmentsupporting
confidence: 93%
See 1 more Smart Citation
“…With this information, the predictive performance of the method should be better than that of using information from past values of FHR alone. This is consistent with our observation in [19]. There we showed that adopting information from UA signals helps in recovering missing samples of FHR tracings.…”
Section: Real Data: Ctg Segmentsupporting
confidence: 93%
“…GPs have been successfully applied in both supervised and unsupervised learning tasks [18]. For example, in our previous work [19], we proposed a GP-based method that employs UA signals to recover missing samples of FHR recordings and had excellent results. This work also provided evidence that the UA signals contain information about fetal well-being.…”
Section: Introductionmentioning
confidence: 99%
“…MAE, RMSE, and W 2 imputation metrics are defined as Different methods of imputation performance were compared in four standard FHR features: the Approximate Entropy (ApEn) [29], Short-Term Variability (STV) [7], Long-Term Variability (LTV), and Δ (Delta) [8]. The formula is defined as follows:…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…The preprocessing step is vital in FHR evaluation, because its quality influences the values of features and, consequently, the evaluation's performance [5][6][7]. For instance, [8] explored the quality of several STV and LTV functions when 0-50% of samples are missing; the functions were randomly picked in a 5 min FHR segment within the initial stage of labor. These missing samples were then linearly interpolated before analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As measurements of FHR using Doppler ultrasound is susceptible to signal dropouts, described in section 2.1.2, any missing data should be estimated prior to any automated analyses. Simple methods such as linear interpolation [61] and cubic Hermite spline interpolation [62], and more complex methods such as Gaussian processes [63] and K-SVD [29] have previously been used to estimate the missing samples on FHR recorded through CTG. However, depending on the length of the gaps, these methods can affect computation of the traditional heart rate features such as variability.…”
Section: Previous Workmentioning
confidence: 99%